Correction to: Acute pulmonary embolism in COVID-19 related hypercoagulability - Cerruti, Lorenzo; Boscaro, Francesca; Poletto, Francesco; Campello, Elena; Spiezia, Luca; Simioni, Paolo (Journal of thrombosis and thrombolysis, 2021)
In the original version of the article, the sequence "name/surname" of the authors was processed incorrectly. The correct sequence (name/surname) is: "Lorenzo Cerruti, Francesca Boscaro, Francesco Poletto, Elena Campello, Luca Spiezia, Paolo Simioni". This has been corrected with this erratum.